A previously undescribed specimen reveals new information on the dentition of Sapeornis chaoyangensis. (June 2017) - Wang, Yan; Hu, Han; O'Connor, Jingmai K.; Wang, Min; Xu, Xing; Zhou, Zhonghe; Wang, Xiaoli; Zheng, Xiaoting
Abstract: Here we describe the well-preserved skull of a juvenile specimen of Sapeornis, STM 16-18. Only the tail and hindlimb plumage of this specimen have been previously described. It preserves what we consider to be the complete dentition of Sapeornis with four premaxillary teeth, three maxillary teeth and two tiny dentary teeth on each side, the latter feature being previously unknown for this taxon. Based on a study of 71 specimens of Sapeornis preserving dentition, we infer the absence of dentary teeth in previously described specimens of Sapeornis is taphonomic, and consider the true dental formula of Sapeornis to be 4-3-2 (premaxillary teeth number – maxillary teeth number – dentary teeth number). Rostral to the dentary teeth, STM 16-18 preserves three shallow, empty aveoli. We hypothesize that this morphology captures an early stage in dental reduction and indicates that in at least some avian lineages, the loss of teeth was gradual.